S‐adenosyl methionine (SAMe) for depression in adults - Galizia, Ilaria (Cochrane Database Syst Rev, 2016)
BACKGROUND: Depression is a recurrent illness with high rates of chronicity, treatment‐resistance and significant economic impact. There is evidence in the literature that S‐adenosyl methionine (SAMe), a naturally occurring compound in the human body, has antidepressant efficacy. This product may be an important addition to the armamentarium of antidepressant agents. OBJECTIVES: To assess the effects of SAMe in comparison with placebo or antidepressants for the treatment of depression in adults. SEARCH METHODS: We searched the Cochrane Common Mental Disorders Group's Specialised Register (CCMDCTR Studies and Reference Register), MEDLINE, EMBASE, PsycINFO, international trial registers ClinicalTrials.gov and the World Health Organization trials portal (ICTRP). We checked reference lists, performed handsearching and contacted experts in the field. The CCMDCTR literature search was last updated on 5 February 2016. SELECTION CRITERIA: Randomised controlled trials comparing SAMe with placebo or antidepressants in adults with a diagnosis of major depression. DATA COLLECTION AND ANALYSIS: Two authors independently performed extraction of data and assessment of risk of bias. We contacted trialists of included studies for additional information. MAIN RESULTS: This systematic review included eight trials comparing SAMe with either placebo, imipramine, desipramine or escitalopram. We accepted trials that used SAMe as monotherapy or as add‐on therapy to selective serotonin reuptake inhibitors (SSRIs), and we accepted both oral and parenteral administration. The review involved 934 adults, of both sexes, from inpatient and outpatient settings. The trials were at low risk of reporting bias. We judged the risk of selection, performance, detection and attrition bias as unclear or low, and one study was at high risk of attrition bias. There was no strong evidence of a difference in terms of change in depressive symptoms from baseline to end of treatment between SAMe and placebo as monotherapy (standardised mean difference (SMD) ‐0.54, 95% confidence interval (CI) ‐1.54 to 0.46; P = 0.29; 142 participants; 2 studies; very low quality evidence). There was also no strong evidence of a difference in terms of drop‐out rates due to any reason between SAMe and placebo, when used as monotherapy (risk ratio (RR) 0.88, 95% CI 0.61 to 1.29; P = 0.52; 142 participants; 2 studies; low quality evidence). Low quality evidence showed that the change in depressive symptoms from baseline to end of treatment was similar between SAMe and imipramine, both as monotherapy (SMD ‐0.04, 95% CI ‐0.34 to 0.27; P = 0.82; 619 participants; 4 studies). There was also no strong evidence of a difference between SAMe and a tricyclic antidepressant in terms of drop‐outs due to any reason (RR 0.61, 95% CI 0.28 to 1.31; P = 0.2; 78 participants; 3 studies; very low quality evidence). There was little evidence of a difference in terms of change in depressive symptoms from baseline to end of treatment between SAMe and escitalopram, both as monotherapy (MD 0.12, 95% CI ‐2.75 to 2.99; P = 0.93; 129 participants; 1 study; low quality evidence). There was no strong evidence of a difference between SAMe and escitalopram in terms of drop‐outs due to any reason (RR 0.81, 95% CI 0.57 to 1.16; P = 0.26; 129 participants; 1 study; low quality evidence). There was low quality evidence that SAMe is superior to placebo as add‐on to SSRIs in terms of change in depressive symptoms from baseline to end of treatment (MD ‐3.90, 95% CI ‐6.93 to ‐0.87; P = 0.01; 73 participants; 1 study). There was no strong evidence of a difference between SAMe and placebo as adjunctive therapy to an SSRI in terms of drop‐outs due to any reason (RR 0.70, 95% CI 0.31 to 1.56; P = 0.38; 73 participants; 1 study; very low quality evidence). For all comparisons, secondary outcome measures of response and remission rates were consistent with these primary outcome measures. With regard to all extractable measures of the acceptability of SAMe, the quality of the evidence was low to very low. SAMe was not different from placebo and established antidepressants. The exception was that compared to imipramine, fewer participants experienced troublesome adverse effects when treated with parenteral SAMe. The specific adverse effects were not detailed in most of the included studies. There were two reports of mania/hypomania recorded for 441 participants in the SAMe arm. AUTHORS' CONCLUSIONS: Given the absence of high quality evidence and the inability to draw firm conclusions based on that evidence, the use of SAMe for the treatment of depression in adults should be investigated further. Future trials should be in the form of large randomised controlled clinical trials of high methodological quality, with particular attention given to randomisation, allocation concealment, blinding and the handling of missing data. Comparator antidepressants from all classes should be used. Adverse events should be detailed for each participant, bearing in mind that induction of mania is of particular interest.